ANALISIS PENGALAMAN PSIKOLOGIS PERAWAT DALAM MENANGANI PASIEN COVID-19 - Ramadhani, Dinda Nur Asri Mutiara; Soedirham, Oedojo (Universitas Tadulako, 2021)
The COVID-19 pandemic shocked the world when a mysterious pneumonia case was discovered from Wuhan City, China on December 31, 2019. The World Health Organization (WHO) named the new virus Severa Acute Respiratory Syndrome Coronavirus-2 (SARS-Cov-2) and the name of the disease. as Corona Virus Disease (Covid-19). Indonesia is ranked 19th with the most Covid-19 cases in the world (Worldometers, 2020). Health workers, including nurses, are at the forefront of dealing with the Covid-19 outbreak. Health care providers, especially nurses, are not only experiencing an increase in workload but also psychological changes that have an impact on the mental health of nurses around the world in the form of burnout, anxiety, depression, and fear of stigma and community discrimination (International Council of Nurses, 2020).